Keakuratan Deteksi Keaslian Sidik Jari Menggunakan Metode Cnn - Hariyanto; Sunny Arief Sudiro; Saepul Lukman (Prosiding Seminar SeNTIK, 2019)
Keakuratan Deteksi Keaslian Sidik Jari Menggunakan Metode Cnn